Displaced and forgotten people? Contradictions regarding residential satisfaction in Bajos de Mena, Puente Alto, Santiago, Chile - Hidalgo Dattwyler, Rodrigo (Revista INVI, 2017)
As a result of the housing expansion into metropolitan peripheries, where subsidiary social housing policies play a fundamental role, there is a sustained occupation of urban limits in cities such as Santiago. Bajos de Mena, in Puente Alto, is not only characterized by its large size and stage-by-stage construction, but also because of the various social and functional problems associated with the buildings, turning this space into a housing paradigm of urban segregation and marginalization. In order to correct these tensions, the Chilean State has designed various methods for intervention through the implementation of a series of programs and projects focused on the areas of education, health care and other social services. This study of residential satisfaction, carried out in four subdivisions of the area under review, questions the concepts of displacement and neglect, which are used to describe the socio-spatial consequences in residential areas such as the one addressed here. This paper also questions the effect of the real-estate market on the production of residential property in Chile.